The Effect of Lactobacillus plantarum CQPC02 on Fatigue and Biochemical Oxidation Levels in a Mouse Model of Physical Exhaustion - Yi, Ruokun; Feng, Min; Chen, Qiuping; Long, Xingyao; Park, Kun-Young; Zhao, Xin (Frontiers in Nutrition, 2021)
Chinese Sichuan pickle is a fermented food rich in microorganisms. Microorganisms have the potential to become an important new form of potent future therapeutic capable of treating human disease. Selecting vitamin C as a positive control, a lactic acid bacteria (Lactobacillus plantarum CQPC02, LP-CQPC02) isolated from Sichuan pickle was given to mice over 4 weeks to investigate the effect of CQPC02 on fatigue levels and biochemical oxidation phenomena in exercise-exhausted Institute of Cancer Research (ICR) mice. The fatigue model was established by forced swimming of mice, the levels of hepatic glycogen, skeletal muscle glycogen, lactic acid, blood urea nitrogen and free fatty acid were measured by physicochemical methods, serum serum creatine kinase (CK), aspartate aminotransferase (AST) and alanine aminotransferase (ALT), superoxide dismutase (SOD), catalase (CAT) and malondialdehyde (MDA) levels were measured by kits, the histopathological changes in the livers of mice were observed by H&E slicing, and the mRNA changes in the livers and skeletal muscles were observed by quantitative polymerase chain reaction (qPCR). Both vitamin C and LP-CQPC02 increased swimming exhaustion time. The concentration of LP-CQPC02 and exhaustion time were positively correlated. LP-CQPC02 also increased liver glycogen, skeletal muscle glycogen and free fatty acid content in mice and reduced lactic acid and blood urea nitrogen content in a dose-dependent manner. As walnut albumin antioxidant peptide concentration increased, levels of mouse CK, AST, and AST gradually decreased. LP-CQPC02 increased SOD and CAT levels and decreased MDA levels in a dose-dependent fashion. LP-CQPC02 up-regulated expression of mRNA encoding copper/zinc-superoxide dismutase (Cu/Zn-SOD), manganese-superoxide dismutase (Mn-SOD), and CAT in swimming exhaustion mouse liver tissue. LP-CQPC02 also up-regulated alanine/serine/cysteine/threonine transporter 1 (ASCT1) expression while down-regulating syncytin-1, inducible nitric oxide synthase (iNOS), tumor necrosis factor-alpha (TNF-α) expression in swimming exhaustion mouse skeletal muscle. Overall, LP-CQPC02 had a clear anti-fatigue and anti-oxidation effect. This suggests that LP-CQPC02 can be developed as a microbiological therapeutic agent.